ANALISIS FAKTOR EKONOMI ALIH USAHATANI KAKAO KE TANAMAN NILAM DI DESA AERE KECAMATAN AERE KABUPATEN KOLAKA TIMUR - Dewi Kurniati; Anas Nikoyan; Suriana Suriana (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studied aim to determine the economic factors that influence the transfer of cocoa farming to patchouli in Aere Village, Aere District, East Kolaka Regency. The implementation of this study was carried out in April 2022 with a total of 30 respondents who transferred cocoa farming to patchouli crops in total. The transfer of farming business carried out by farmers in Aere Village is to change the cultivation of farming businesses that used to be cocoa to patchouli plants. The data analysis used is to determine the difference in the amount of income receipts of farmers before transferring farming and after transferring farming. The results showed that the amount of income receipts of farmers who transferred cocoa farming to patchouli crops in Aere Village, Aere District, East Kolaka Regency had a considerable difference where the average income of cocoa farmers before switching was Rp. 132.300.564,-/ year and after switching to patchouli crops, the average income of farmers was Rp. 517.309.571,-/ year